2015
DOI: 10.1007/s12288-015-0569-3
|View full text |Cite
|
Sign up to set email alerts
|

l-carnitine as a Potential Additive in Blood Storage Solutions: A Study on Erythrocytes

Abstract: Erythrocytes undergo various changes during storage (storage lesion) that in turn reduces their functioning and survival. Oxidative stress plays a major role in the storage lesion and antioxidants can be used to combat this stress. This study elucidates the effects of L-carnitine (LC) on erythrocytes of stored blood. Blood was obtained from male Wistar rats and stored (4°C) for 20 days in CPDA-1 (citrate phosphate dextrose adenine) solution. Samples were divided into-(i) controls (ii) LC 10 (L-carnitine at a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Blood samples obtained were grouped into controls – LC 10, LC 30 and LC 60 – and stored in CPD‐A solution at 4 °C for 55 days as depicted in Table . The experimental concentrations were chosen on the basis of literature review (Arduini et al ., ; Sweeney & Arduini, ; Arduini et al ., ) and our prior studies on ROS (Soumya & Vani, ) and rat blood (Soumya et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Blood samples obtained were grouped into controls – LC 10, LC 30 and LC 60 – and stored in CPD‐A solution at 4 °C for 55 days as depicted in Table . The experimental concentrations were chosen on the basis of literature review (Arduini et al ., ; Sweeney & Arduini, ; Arduini et al ., ) and our prior studies on ROS (Soumya & Vani, ) and rat blood (Soumya et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The experimental concentrations were chosen on the basis of literature review 10,12,13 and our prior studies on ROS 16 and rat blood. 14…”
Section: Blood Sampling and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have reported on the effects of L-carnitine on other blood components (erythrocytes and platelets) [ 8 , 9 , 10 , 11 ]. Although there are reports on plasma storage [ 12 , 13 , 14 , 15 ], very few have focused on plasma isolated from stored blood.…”
Section: Introductionmentioning
confidence: 99%